Guardians of Islam : Religious Authority and Muslim Communities of Late Medieval Spain. - Miller, Kathryn A. (Columbia University Press, 2008)
Muslim enclaves within non-Islamic polities are commonly believed to have been beleaguered communities undergoing relentless cultural and religious decline. Cut off from the Islamic world, these Muslim groups, it is assumed, passively yielded to political, social, and economic forces of assimilation and acculturation before finally accepting Christian dogma. Kathryn A. Miller radically reconceptualizes what she calls the exclave experience of medieval Muslim minorities. By focusing on the legal scholars (faqihs) of fifteenth-century Aragonese Muslim communities and translating little-known an.